THE INFLUENCE OF THE ROLES OF SCHOOL SUPERVISORS AND PRINCIPALS ON THE QUALITY OF PUBLIC ELEMENTARY SCHOOL: A CASE STUDY IN REMBANG DISTRICT REMBANG REGENCY - Wahyuni Rahma Dianti; Ngasbun Egar; Ghufron Abdullah (SOSIOEDUKASI, 2025)
This study aims to examine the influence of the roles of school supervisors and principals on the quality of public elementary schools in Rembang District, Rembang Regency. Using a quantitative correlational approach, data were collected through a Likert-scale questionnaire distributed to 188 teachers from 45 public elementary schools. The research focuses on three main variables: school quality (dependent), the role of school supervisors, and the role of principals (independent). The results indicate that both school supervisors and principals have a statistically significant influence on school quality, both partially and simultaneously. However, the direction of influence is negative, suggesting that increased perception of their roles tends to appear in schools experiencing lower performance. Factor analysis reveals that managerial supervision by supervisors and the supervisory role of principals are the most dominant dimensions perceived by teachers. The novelty of this study lies in its finding that strong perceived leadership roles do not always correlate positively with school quality, especially when such roles are implemented as responses to existing problems. The study is limited by its use of perception-based data and cross-sectional design. Future research is recommended to adopt mixed methods, include objective school quality indicators, and use longitudinal data for broader and deeper insights